Communication of Married Couple Affected by Layoffs During the Covid-19 In Lamongan, East Java - Ja'far Shodiq; Devi Kasumawati (Alhurriyah, 2023)
The COVID-19 epidemic has had a significant impact on the lives of people all over the world, particularly in the economic sphere, which has driven to a strategy of eliminating employees (PHK). Some individuals, including those in the Lamongan Regency, were laid off. Therefore, the family's primary source of income stagnates. In fact, living is one of the most essential elements for constructing a sakinah family. In 2021, there are 455 divorce cases in the Lamongan Regency, of which 40% are a result of family economic crisis. Therefore, it is fascinating to examine how husbands and wives who were laid off during the Covid-19 pandemic interacted to establish a sakinah household.Pandemi COVID-19 telah memberikan pengaruh pada kehidupan masyarakat di dunia, terutama di bidang ekonomi yang menyebabkan adanya kebijakan pengurangan tenaga kerja melalui pemutusan hubungan kerja (PHK). Sebagian masyarkat kehilangan pekerjaannya, termasuk di Kabupaten Lamongan. Sehingga sumber pemasukan untuk memberi nafkah pada keluarga menjadi terhenti. Padahal, nafkah menjadi salah satu komponen penting untuk membina keluarga yang sakinah. Pada tahun 2021, terdapat 455 kasus perceraian di Kabupaten Lamongan dan 40% disebabkan oleh masalah ekonomi keluarga. Dengan demikian, menjadi menarik untuk meneliti cara komunikasi suami-istri yang terkena PHK selama masa pandemi Covid-19 untuk mewujudkan keluarga yang sakinah.